Extensive text on back: 'Gli anarchici hanno dedicato un monumento marmoreo al loro campagno Franco Serantini ...'
Extensive text on back: 'Gli anarchici hanno dedicato un monumento marmoreo al loro campagno Franco Serantini ...'.